2021
DOI: 10.1038/s41598-021-82490-z
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter evaluation of Verigene Enteric Pathogens Nucleic Acid Test for detection of gastrointestinal pathogens

Abstract: We investigated the efficiency of the Verigene Enteric Pathogens Nucleic Acid Test (Verigene EP test), which is an automated microarray-based assay system that enables rapid and simultaneous genetic detection of gastrointestinal pathogens and toxins, including those in the Campylobacter Group, Salmonella species, Shigella species, the Vibrio Group, Yersinia enterocolitica, Shiga toxin 1 and 2, norovirus GI/GII, and rotavirus A. Three clinical laboratories evaluated the Verigene EP test, using 268 stool samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Several multiplex molecular assays have been developed and used in clinical settings for other types of POCT. These systems can detect multiple pathogens with high sensitivity 16,17 and are beneficial for vulnerable individuals, such as hospitalized or immunocompromised patients. 18 Appropriate use of each type of POCT is crucial, in different clinical settings.…”
Section: Ta B L Ementioning
confidence: 99%
See 1 more Smart Citation
“…Several multiplex molecular assays have been developed and used in clinical settings for other types of POCT. These systems can detect multiple pathogens with high sensitivity 16,17 and are beneficial for vulnerable individuals, such as hospitalized or immunocompromised patients. 18 Appropriate use of each type of POCT is crucial, in different clinical settings.…”
Section: Ta B L Ementioning
confidence: 99%
“…Nevertheless, our study indicated that microscopic examinations by physicians could not reliably rule out Campylobacter infection. Antigen testing showed higher sensitivity than microscopic examinations, and the interpretation of the test results can be more objective, although evaluated only in a small study population 10,19 and not commercially Multiplex molecular assays have demonstrated excellent diagnostic performance 16,17 ; however, the requirement of special equipment and expensive examination cost can limit their clinical usefulness. Given that most patients with gastroenteritis suffer mild illnesses in the primary care settings, the use of multiplex molecular assays should be reserved for hospitalized or emergency department patients.…”
Section: Ta B L Ementioning
confidence: 99%